Use of unlicensed drugs and off-label drug use: focus on COVID-19 - S. A. Mishinova; A. A. Zhuravkov; V. K. Zhuravko (Izdatelstvo OKI, 2020)
Introduction. In a crisis, like the COVID-19 outbreak, the strategy of experimental drug use in clinical practice increases the availability of potentially effective drugs that have not yet proven the opposite for patients with life-threatening diseases, despite the fact that such use is «off-label» for unregistered indications. The choice of drugs for «off-label» use is most difficult when a large potential benefit justifies higher risks, because the use of drugs for unapproved indications increases the frequency of adverse drug reactions and thereby reduces their clinical value. Goal. Clinical and pharmacological analysis of the «off-label» features of drug use for etiotropic and pathogenetic therapy of COVID-19, description of new opportunities for state registration of medicines in the fight against a new coronavirus infection. Materials and methods. From the Russian temporary guidelines for the treatment of COVID-19 were identified 14 international non-generic names (INN) of drugs. We analyzed the data obtained for the corresponding INN in the State register of medicines of the Ministry of health of the Russian Federation. Results. There is a widespread violation of the requirements of various sections of the current instructions for the medical use of the considered drugs, which requires additional analysis of real-word data. Conclusions. For this purpose, we can use thematic reports, patient registers, and active post-marketing pharmacovigilance.